PELEBARAN RUAS JALAN GUNUNG SARI – MANCAK – ANYER - An An Anisarida; Sri Handayani (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
The growth of road infrastructure in Indonesia is increasing in line with the growth in traffic volume. Roads that function as a means of connecting between humans and land use in order to increase road capacity require widening. Jalan Gunungsari - Mancak - Anyer is a provincial road that has always been used as an alternative road to the Anyer tourist area, currently the condition of the existing road width does not meet provincial road standards where the minimum width is approximately 7 meters so that a handling is needed by widening the Gunungsari - Mancak - Anyer road section so that it can increase road capacity on this road section, so that a handling system arrangement is needed so that there are no obstacles or blockages and optimal service. Planning for widening this road using the Road Pavement Manual method Number 04/SE/Db/2017 obtained that the thickness of the Hotmix (AC – WC) surface layer is 6 cm, the thickness of the upper foundation layer (aggregate) class A is 16 cm, the lower foundation layer (aggregate) class B is 24 cm with a design life of 10 years.